The Effect Of Co-Op-Co-Op Learning Model Towards Students’ Self Efficacy In Speaking Competence - Sri Ariani; Eki Hendrawan (JUPE : Jurnal Pendidikan Mandala, 2020)
This research aims to determine the effect of co-op-co-op on students' self-efficacy in speaking to the  second grade students of Al-Ashriyah Gunungsari. This research is pre-experimental study with one group pretest-posttest design. The sample of this study consisted of 42 students; oral test is used as the instrument in this study. Pre-test and post-test are applied for one class. Data analysis techniques of this resaearch used descriptive statistics and inferential statistics. The findings of the study showed that the t-test was 111.7 and the t-table value was 1,684 with 40 degrees of freedom in the 0.05% confidence level. This shows that the alternative hypothesis (Ha) is accepted. It is revealed that the experimental average score is high. It concluded that the co-op-co-op method has significant effect in teaching speaking to second grade students of Al-Ashriyah Gunungsari. Based on the result  of this research, it is reccomended for the teachers to apply co-op-co-op in teaching speaking for the students.